PET-based composite copper foil as well as preparation method and application thereof
Through O2 plasma etching, NaOH modification and silver ammonia activation treatment combined with electroless copper plating, the problem of weak interface bonding force of PET-based composite copper foil is solved, low-cost and high-strength Cu layer deposition is achieved, and it is suitable for the current collector manufacturing of lithium-ion batteries.
Patent Information
- Application Number
- CN202510751734.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-06
- Publication Date
- 2025-08-05
AI Technical Summary
In the prior art, the use of electrolytic copper foil as the current collector in the negative electrode of the traditional lithium-ion battery has problems such as high material density and insufficient mechanical ductility. In the preparation of the composite current collector, the electroless copper plating process has problems such as weak interface bonding force and easy copper layer to fall off, resulting in high production costs.
Using O2 plasma etching, NaOH modification and silver ammonia activation treatment combined with electroless copper plating, micro-nano-scale rough structures and active functional groups are constructed on the surface of PET film to form a uniform catalytic center to achieve effective deposition of Cu.
The production cost of composite copper foil is reduced, the bonding strength between the Cu layer and the PET substrate is increased, and the defects of the physical vapor deposition process are avoided, and a dense and uniform copper layer is prepared.
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of current collector preparation, and in particular relates to a PET copper foil, a preparation method and an application thereof. Background Art
[0002] With the rapid growth in demand for high-energy-density lithium-ion batteries in new energy vehicles and portable electronic devices, battery lightweighting has become a key technological development direction. Conventional lithium-ion battery anodes use electrolytic copper foil as the current collector, typically with a thickness of 6-12 μm. However, pure metal copper foil suffers from high material density (8.96 g / cm³) and insufficient mechanical ductility, hindering further improvements in battery energy density. Furthermore, due to limitations in production processes and the inherent mechanical strength of electrolytic copper foil, further weight reduction by reducing copper foil thickness is difficult. Consequently, the exploration of sandwich-structured composite copper foil current collectors based on polymer substrates (PI, PET, PP) is gaining increasing attention.
[0003] Currently, composite current collectors are primarily prepared using a combination of magnetron sputtering and electroplating. Patent CN116207270A uses plasma or NaOH etching followed by magnetron sputtering and electroplating to produce composite copper foil. However, this method suffers from high equipment investment, low deposition rate, and thin film perforation. Chemical copper plating offers unique advantages due to its ability to autocatalytically deposit on non-conductive substrates without requiring an external power source. However, existing chemical copper plating processes still suffer from weak polymer / metal interface bonding in composite current collector preparation, leading to delamination after cyclic charge and discharge cycles. Patent CN117702095A proposes a method for preparing composite copper foil by chemically plating copper on a polyvinyl chloride (PI) surface. Although PI is highly compatible with chemical plating processes and can effectively improve the interfacial bonding of composite copper foil, its high material cost limits its industrial application. In comparison, PET is inexpensive, but its surface is inert and difficult to modify and activate. Consequently, composite copper foils prepared by chemical plating have low interfacial bonding strength and the copper layer is prone to detachment. Patent CN119372733A proposes a method for electroless copper plating on PET surfaces. However, this process relies on the expensive precious metal Pd as an activator to improve coating adhesion, significantly increasing the production cost of composite copper foil. Patent CN119764455A uses plasma etching and NaOH treatment to roughen the PI film, but this method still requires the use of the precious metal Pd as an activator and involves subsequent electroplating thickening, making one-step electroless plating impossible and the preparation process cumbersome.
[0004] In summary, the magnetron sputtering + electroplating production process can lead to perforations and wrinkles in the polymer interlayer, reducing the yield of the composite copper foil. While electroless plating can avoid these issues, it relies on expensive Pd metal activators and suffers from insufficient copper layer adhesion and easy copper detachment. Therefore, it is crucial to achieve surface modification and activation of the inert PET and a copper layer with good electroless plating adhesion without using expensive Pd. Summary of the Invention
[0005] In order to solve the problems existing in the prior art, the present invention provides a Cu-PET-Cu composite copper foil based on chemical plating and its preparation method and application, aiming to achieve effective deposition of Cu using a relatively low-cost PET surface.
[0006] As one aspect of the present invention, a method for preparing a PET-based composite copper foil is provided. The method is achieved by electroless plating Cu on both sides of the PET, and specifically comprises the following steps:
[0007] 1) etching the PET film using O2 plasma, wherein the etching power is 20-100W, the oxygen flow rate is 5-40sccm, and the etching time is 1-10 minutes to obtain a functionalized PET film;
[0008] 2) modifying the functionalized PET film, within 10 minutes of obtaining the functionalized PET film in step 1), placing the functionalized PET film in a NaOH solution having a concentration of 80 to 180 g / L for modification for 50 to 100 minutes to obtain a modified PET film;
[0009] 3) activating the modified PET film, activating the modified PET film in a silver ammonia solution having a silver ion concentration of 0.1 to 5 g / L to obtain an activated PET film;
[0010] 4) chemical copper plating, immersing the activated PET film obtained in step 3) in a chemical copper plating solution for chemical copper plating to obtain a PET-based composite copper foil, wherein the chemical copper plating solution comprises two or more of 1-10 mg / L potassium ferrocyanide, 5-20 mg / L 2,2'-bipyridine, 20-50 mg / L polyethylene glycol 6000, 1-10 mL / L tetrahydroxypropyl ethylenediamine, 1-10 mg / L thiourea, 0.1-5 mg / L sodium lauryl sulfate, and 1 mg / L-10 mg / L 2,2-quinoline, measured by the total volume of the chemical copper plating solution.
[0011] As a preferred embodiment of the method for preparing a PET-based composite copper foil of the present invention, the method further includes a step of pretreating the PET film before etching, wherein the pretreatment comprises: immersing the PET film in anhydrous ethanol, degreasing the film under ultrasound at a power of 40 to 100 W for 1 to 10 minutes, removing the film and rinsing it with deionized water, and then immersing the film in 1 to 10 wt% dilute sulfuric acid and ultrasound for 1 to 10 minutes.
[0012] As a preferred embodiment of the method for preparing a PET-based composite copper foil of the present invention, the thickness of the PET film is 4 to 20 μm.
[0013] As a preferred embodiment of the method for preparing a PET-based composite copper foil of the present invention, the temperature of the modification treatment is 25-70°C.
[0014] As a preferred embodiment of the method for preparing a PET-based composite copper foil of the present invention, the activation treatment is performed at a temperature of 26-60° C. and for a time of 1-10 minutes.
[0015] As a preferred embodiment of the method for preparing a PET-based composite copper foil of the present invention, the temperature of the chemical copper plating is 40-70° C., and the time is 10-30 minutes.
[0016] As a preferred embodiment of the method for preparing a PET-based composite copper foil of the present invention, the chemical copper plating solution further comprises 2-15 g / L copper sulfate, 10-50 g / L tetrasodium ethylenediaminetetraacetic acid, 5-15 g / L formaldehyde, and 5-20 g / L NaOH.
[0017] As another aspect of the present invention, a PET-based composite copper foil is provided, wherein the composite copper foil is prepared by any of the aforementioned methods, wherein the thickness of the copper foil on both sides of the PET is 0.6 to 1.5 μm, and the copper layer bonding strength of the PET-based composite copper foil is ≥3N / cm 2 .
[0018] As another aspect of the present invention, there is provided a use of the aforementioned PET-based composite copper foil in a negative electrode current collector.
[0019] As another aspect of the present invention, there is provided an application of the aforementioned PET-based composite copper foil in a battery.
[0020] The innovative concept of the present invention is described in detail below:
[0021] About Etching
[0022] Compared with substrates such as PI, the PET substrate selected in the present invention is inexpensive, but it has the problems of strong surface inertness and poor wettability. Based on this, the present invention creatively proposes to use O2 plasma etching technology to etch the surface of the PET film. Through etching, rich oxygen-containing polar functional groups can be introduced into the PET surface, and micro-nanoscale rough structures can be constructed. This dual modification effect significantly improves the surface energy of the PET film, while increasing the contact area with the NaOH solution, which is beneficial to the subsequent NaOH modification treatment. In this step, the power, oxygen flow and time parameters are particularly critical. When the power is too low and the treatment time is too short, the surface of the PET film cannot be effectively functionalized, the surface roughness is low and there is a lack of oxygen-containing groups, resulting in low wettability of the PET film to the NaOH solution and inability to undergo modification reaction with hydroxide ions, thereby affecting the subsequent silver activation and copper chemical plating reactions; when the power and treatment time are too high, the surface of the PET film will be over-etched, forming deep pits or perforations, which will reduce the mechanical properties of the material; therefore, in the technical solution of the present invention, the etching power is determined to be 20~100 W, specifically, it can be 20W, 30W, 50W, 60W, 100W and the range of any two values thereof; the oxygen flow rate is 5~40 sccm, specifically, it can be 5sccm, 10sccm, 12sccm, 15sccm, 18sccm, 25sccm, 36sccm, 40sccm and the range of any two values thereof; the etching time is 1~10 min, specifically, it can be 1 min, 2 min, 4 min, 5 min, 7 min, 8 min, 9 min, 10 min and an interval consisting of any two values.
[0023] About the interval time
[0024] During the experimental process of the present invention, it was creatively discovered that the interval between the etching treatment and the modification treatment has a significant impact on the modification effect and the subsequent bonding strength between Cu and the substrate. Specifically, when the interval time is too long, the etching modification effect of the plasma decreases rapidly, and the oxygen-containing functional groups on the surface of the PET film gradually disappear. Therefore, based on the solution of the present invention, it is determined that the modification treatment is performed within 10 minutes after the etching treatment is completed. Furthermore, the interval time can be further compressed to, for example, within 8 minutes, 6 minutes, 5 minutes, 3 minutes, or 1 minute.
[0025] About modification treatment
[0026] The purpose of the modification treatment of the present invention is to obtain active sites to further convert Ag +The present invention forms a uniform catalytic center on the surface of the PET film, thereby enhancing the interface bonding strength between the film and Cu. + The integration of the present invention provides effective active sites. Although most alkaline substances can provide active functional groups such as -COOH and -OH, the present invention creatively discovered that when NaOH solution is selected as the modifier, it has superior performance. This is because no additional metal ions are introduced and the cost is low. Based on the technical solution of the present invention, the concentration of NaOH is determined to be 50~180g / L. Specifically, it can be 50g / L, 65g / L, 80g / L, 90g / L, 100g / L, 110g / L, 125g / L, 135g / L, 140g / L, 160g / L, 180g / L and the interval consisting of any two values thereof. Furthermore, the temperature and duration of the modification treatment also affect the provision of active sites. When the modification temperature is too low or the treatment time is too short, insufficient active sites are formed, resulting in a small number of subsequent catalytic centers and uneven distribution, which affects the plating effect of the Cu layer. When the modification temperature is too high or the treatment time is too long, the PET film surface is further etched, causing wrinkles in the PET film, which affects activation and the electroless Cu plating process. Based on the technical solution of the present invention, the modification temperature is selected to be 25-70°C, specifically 25°C, 30°C, 36°C, 45°C, 50°C, 60°C, 70°C, or any two thereof. The modification time is selected to be 10-100 minutes, specifically 10 minutes, 20 minutes, 40 minutes, 50 minutes, 70 minutes, 80 minutes, 90 minutes, 100 minutes, or any two thereof.
[0027] About activation treatment
[0028] The purpose of the activation treatment of the present invention is to form uniform catalytic centers on the surface of the PET film, so as to facilitate the reduction and precipitation of Cu in the chemical copper plating step and thus improve the bonding strength between the Cu layer and the substrate. + Activation treatment to form catalytic centers can significantly improve the bonding strength between Cu and the substrate. This is because Ag⁺ is reduced to Ag nanoparticles (Ag 0 ), adsorbed on the PET surface, forming a seed layer with high catalytic activity, providing nucleation sites for subsequent chemical copper plating. In addition, Ag +Concentration also has a significant impact on the activation effect. When the concentration is too low, the density of metal active sites on the PET film surface that catalyze copper ion deposition is low, and it cannot effectively catalyze the reduction and deposition of copper ions in the chemical copper plating solution on the PET film surface. When the concentration is too high, it causes Ag nanoparticles to agglomerate, reducing catalytic activity. Based on the solution of the present invention, the concentration of silver ions in the silver ammonia solution is determined to be 0.1-10 g / L. Specifically, it can be 0.1, 0.3 g / L, 0.5 g / L, 0.8 g / L, 1 g / L, 1.8 g / L, 2.5 g / L, 3 g / L, 4 g / L, 5 g / L, 6.5 g / L, 7.5 g / L, 8 g / L, 9 g / L, 10 g / L, and an interval consisting of any two of these values.
[0029] About copper plating reagents
[0030] During the experimental process of the present invention, it was creatively discovered that the type and quantity of additives in the chemical copper plating solution have a significant impact on the copper plating effect. When only one additive of the present invention is used, the stability of the chemical copper plating solution decreases and self-decomposition occurs. The copper ion deposition is too rapid, resulting in an increase in copper layer defects. The resulting copper layer is severely delaminated and the interfacial bonding strength is significantly degraded. Based on this, it is determined that the additives of the chemical copper plating solution of the present invention include 1-10 mg / L potassium ferrocyanide, 5-20 mg / L 2,2'-bipyridine, 20-50 mg / L polyethylene glycol 6000, 1-5 mL / L tetrahydroxypropyl ethylenediamine, 1-10 mg / L thiourea, 0.1-5 mg / L sodium lauryl sulfate, and 1 mg / L-10 mg / L 2,2-quinoline. Two or more of these are selected.
[0031] About the order of steps
[0032] As mentioned above, the purpose of the etching treatment of the present invention is to introduce abundant oxygen-containing polar functional groups to the PET surface and construct a micro-nanoscale rough structure. This dual modification significantly increases the surface energy of the PET film and increases the contact area with the NaOH solution, which is beneficial to the subsequent NaOH modification treatment. The purpose of the modification treatment is to obtain active sites and then Ag + The activation treatment is designed to form uniform catalytic centers on the surface of the PET film, facilitating the reduction and precipitation of Cu during the electroless copper plating step, thereby improving the bonding strength between the Cu layer and the substrate. As can be seen, each step follows a strict sequence, with each step laying the foundation for the subsequent steps. Therefore, to achieve improved bonding strength between the Cu layer and the substrate, the order of etching, modification, and activation must be followed.
[0033] Furthermore, it should be noted that the amounts of solution reagents used in the modification, activation, and electroless copper plating steps of the present invention do not require specific limitations and can be used in amounts commonly used in the art, such as amounts sufficient to completely immerse the PET film in the reagents. For electroless copper plating, "measured in units of the total electroless copper plating solution volume" refers to the amount of each solute added calculated based on the total volume of the electroless copper plating solution (in L). For example, "1-10 mg / L potassium ferrocyanide" means 1-10 mg of potassium ferrocyanide per liter of copper plating solution. The same conversion method applies to other groups.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. The present invention adopts PET substrate to realize the preparation of composite copper foil, successfully avoiding the bottleneck problem of PI material and high price, and greatly reducing the cost of composite copper foil;
[0036] 2. The present invention obtains a composite copper foil with excellent bonding properties by adopting the method of etching → modification → activation → chemical plating, which can be effectively used in the manufacture of current collectors and batteries;
[0037] 3. Compared with traditional physical vapor deposition methods such as magnetron sputtering and vacuum evaporation, the chemical plating of the present invention has the advantages of low equipment investment cost and no need for complex high-temperature and high-vacuum systems. In addition, the copper layer prepared by the chemical copper plating method has a dense structure, good uniformity, and no holes, avoiding the problems of thin film perforation and poor coating uniformity that may be caused by the physical vapor deposition process. DETAILED DESCRIPTION
[0038] The following will be a clear and complete description of the technical solutions in the embodiments. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.
[0039] Example 1
[0040] A method for preparing a PET-based composite copper foil comprises the following steps:
[0041] 1) Using a 4-μm PET film as the reaction substrate, the film was immersed in anhydrous ethanol and degreased under ultrasonication at a power of 50 W for 5 minutes. The film was then removed and rinsed with deionized water and immersed in 5 wt% dilute sulfuric acid for 5 minutes. The surface of the PET film was then etched using O2 plasma at a power of 40 W, an oxygen flow rate of 30 sccm, and an etching time of 5 minutes to obtain a functionalized PET film.
[0042] 2) Prepare a 150 g / L NaOH solution. 5 minutes after step 1), completely immerse the functionalized PET film in the solution and modify it at 50°C for 60 minutes to obtain a modified PET film. Prepare a 1 g / L AgNO3 solution and slowly add 1 wt% ammonia water dropwise until the precipitate completely disappears to obtain a silver ammonia solution (at this point, the silver ion concentration of the silver ammonia solution is 0.6 g / L). Completely immerse the modified PET film in the silver ammonia solution and activate it at 50°C for 10 minutes to obtain an Ag-activated PET film.
[0043] 3) Based on the total volume of the electroless copper plating solution, an electroless copper plating solution was prepared according to the following conditions: copper sulfate concentration of 10 g / L (i.e., 10 g of copper sulfate is contained in 1 L of electroless copper plating solution, the same below), tetrasodium EDTA concentration of 30 g / L, formaldehyde concentration of 10 g / L, NaOH concentration of 10 g / L, potassium ferrocyanide concentration of 2 mg / L, 2,2'-bipyridine concentration of 15 mg / L, polyethylene glycol 6000 concentration of 30 mg / L, tetrahydroxypropyl ethylenediamine concentration of 5 mL / L, and the balance of water. The Ag-activated PET film was completely immersed in the copper plating solution and copper plating was performed at 50°C for 30 min to obtain a 6-μm composite copper foil. The thickness of the copper foil on both sides of the PET was 1 μm.
[0044] The copper layer is dense, uniform and has no holes. The peel strength test shows that the copper layer bonding strength is 4N / cm 2 , meeting the basic requirements of composite copper foil.
[0045] Example 2
[0046] 1) Using a 4-μm PET film as the reaction substrate, the film was immersed in anhydrous ethanol and degreased under ultrasonication at a power of 50 W for 5 minutes. The film was then removed and rinsed with deionized water and immersed in 5 wt% dilute sulfuric acid for 5 minutes. The surface of the PET film was then etched using O2 plasma at a power of 80 W, an oxygen flow rate of 30 sccm, and an etching time of 2 minutes to obtain a functionalized PET film.
[0047] 2) Prepare a 100 g / L NaOH solution. 5 minutes after step 1), completely immerse the functionalized PET film in the solution and modify it at 50°C for 60 minutes to obtain a modified PET film. Prepare a 1 g / L AgNO3 solution and slowly add 1 wt% ammonia water dropwise until the precipitate completely disappears to obtain a silver-ammonia solution. Completely immerse the modified PET film in the silver-ammonia solution and activate it at 50°C for 10 minutes to obtain an Ag-activated PET film.
[0048] 3) Based on the total volume of the electroless copper plating solution, an electroless copper plating solution was prepared with a concentration of 10 g / L copper sulfate, 30 g / L tetrasodium EDTA, 10 g / L formaldehyde, 10 g / L NaOH, 2 mg / L potassium ferrocyanide, 5 mg / L 2,2'-bipyridine, 50 mg / L polyethylene glycol 6000, and 5 mL / L tetrahydroxypropylethylenediamine. The Ag-activated PET film was completely immersed in the copper plating solution and copper plating was performed at 50°C for 30 min. Finally, a 6-μm composite copper foil with good bonding strength was obtained. The thickness of the copper foil on both sides of the PET was 1 μm.
[0049] The copper layer is dense, uniform and has no holes. The peel strength test shows that the copper layer bonding strength is 3.8N / cm. 2 , meeting the basic requirements of composite copper foil.
[0050] Example 3
[0051] A method for preparing a PET-based composite copper foil comprises the following steps:
[0052] 1) Using a 4-μm PET film as the reaction substrate, the film was immersed in anhydrous ethanol and degreased under ultrasonication at a power of 50 W for 5 minutes. After removal, the film was rinsed with deionized water and immersed in 5 wt% dilute sulfuric acid and ultrasonicated for 5 minutes. The surface of the PET film was then etched using O2 plasma at a power of 20 W, an oxygen flow rate of 20 sccm, and an etching time of 10 minutes to obtain a functionalized PET film.
[0053] 2) Prepare a 150 g / L NaOH solution. 5 minutes after step 1), completely immerse the functionalized PET film in the solution and modify it at 50°C for 60 minutes to obtain a modified PET film. Prepare a 1 g / L AgNO3 solution and slowly add 1 wt% ammonia solution until the precipitate completely disappears to obtain a silver-ammonia solution. Completely immerse the modified PET film in the silver-ammonia solution and activate it at 50°C for 10 minutes to obtain an Ag-activated PET film.
[0054] 3) Prepare an electroless copper plating solution based on the total volume of the electroless copper plating solution, with a concentration of 10 g / L copper sulfate, 30 g / L tetrasodium EDTA, 10 g / L formaldehyde, 10 g / L NaOH, 10 mg / L potassium ferrocyanide, 10 mg / L 2,2'-bipyridine, 25 mg / L polyethylene glycol 6000, and 5 mL / L tetrahydroxypropylethylenediamine. Completely immerse the Ag-activated PET film in the copper plating solution and plate the film at 50°C for 30 min to obtain a 6-μm composite copper foil. The thickness of the copper foil on both sides of the PET film is 1 μm.
[0055] The copper layer is dense, uniform and has no holes. The peel strength test shows that the copper layer bonding strength is 3.5N / cm. 2 , meeting the basic requirements of composite copper foil.
[0056] Example 4
[0057] A method for preparing a PET-based composite copper foil comprises the following steps:
[0058] 1) Using a 4-μm PET film as the reaction substrate, the film was immersed in anhydrous ethanol and degreased under ultrasonication at a power of 50 W for 5 minutes. The film was then removed and rinsed with deionized water and immersed in 5 wt% dilute sulfuric acid for 5 minutes. The surface of the PET film was then etched using O2 plasma at a power of 40 W, an oxygen flow rate of 30 sccm, and an etching time of 5 minutes to obtain a functionalized PET film.
[0059] 2) Prepare a 100 g / L NaOH solution. 5 minutes after step 1), completely immerse the functionalized PET film in the solution and modify it at 50°C for 70 minutes to obtain a modified PET film. Prepare a 1 g / L AgNO3 solution and slowly add 1 wt% ammonia solution until the precipitate completely disappears to obtain a silver-ammonia solution. Completely immerse the modified PET film in the silver-ammonia solution and activate it at 50°C for 10 minutes to obtain an Ag-activated PET film.
[0060] 3) Based on the total volume of the electroless copper plating solution, an electroless copper plating solution was prepared with a concentration of 10 g / L copper sulfate, 30 g / L tetrasodium EDTA, 10 g / L formaldehyde, 10 g / L NaOH, 5 mg / L potassium ferrocyanide, 10 mg / L 2,2'-bipyridine, 30 mg / L polyethylene glycol 6000, and 5 mL / L tetrahydroxypropylethylenediamine. The Ag-activated PET film was completely immersed in the copper plating solution and copper plating was performed at 50°C for 30 min to obtain a 6-μm composite copper foil with a thickness of 1 μm on both sides of the PET film.
[0061] The copper layer is dense, uniform and has no holes. The peel strength test shows that the copper layer bonding strength is 3.6N / cm. 2 , meeting the basic requirements of composite copper foil.
[0062] Example 5
[0063] A method for preparing a PET-based composite copper foil comprises the following steps:
[0064] 1) Using a 4-μm PET film as the reaction substrate, the film was immersed in anhydrous ethanol and degreased under ultrasonication at a power of 50 W for 5 minutes. The film was then removed and rinsed with deionized water and immersed in 5 wt% dilute sulfuric acid for 5 minutes. The surface of the PET film was then etched using O2 plasma at a power of 40 W, an oxygen flow rate of 30 sccm, and an etching time of 5 minutes to obtain a functionalized PET film.
[0065] 2) Prepare a 150 g / L NaOH solution. 5 minutes after step 1), completely immerse the functionalized PET film in the solution and modify it at 50°C for 60 minutes to obtain a modified PET film. Prepare a 0.5 g / L AgNO3 solution and slowly add 1 wt% ammonia water dropwise until the precipitate completely disappears to obtain a silver ammonia solution (at this point, the concentration of the silver ammonia solution is 0.3 g / L). Completely immerse the modified PET film in the silver ammonia solution and activate it at 50°C for 10 minutes to obtain an Ag-activated PET film.
[0066] 3) Prepare an electroless copper plating solution based on the total volume of the electroless copper plating solution, with a concentration of 10 g / L copper sulfate, 30 g / L tetrasodium EDTA, 10 g / L formaldehyde, 10 g / L NaOH, 5 mg / L potassium ferrocyanide, 5 mg / L 2,2'-bipyridine, 20 mg / L polyethylene glycol 6000, and 10 mL / L tetrahydroxypropylethylenediamine. Completely immerse the Ag-activated PET film in the copper plating solution and perform copper plating at 50°C for 30 min to obtain a 6-μm composite copper foil with a thickness of 1 μm on both sides of the PET film.
[0067] The copper layer is dense, uniform and has no holes. The peel strength test shows that the copper layer bonding strength is 3.4N / cm. 2 , meeting the basic requirements of composite copper foil.
[0068] Example 6
[0069] A method for preparing a PET-based composite copper foil comprises the following steps:
[0070] 1) Using a 4-μm PET film as the reaction substrate, the film was immersed in anhydrous ethanol and degreased under ultrasonication at a power of 50 W for 5 minutes. The film was then removed and rinsed with deionized water and immersed in 5 wt% dilute sulfuric acid for 5 minutes. The surface of the PET film was then etched using O2 plasma at a power of 40 W, an oxygen flow rate of 30 sccm, and an etching time of 5 minutes to obtain a functionalized PET film.
[0071] 2) Prepare a 150 g / L NaOH solution. 5 minutes after step 1), completely immerse the functionalized PET film in the solution and modify it at 50°C for 60 minutes to obtain a modified PET film. Prepare a 1 g / L AgNO3 solution and slowly add 1 wt% ammonia solution until the precipitate completely disappears to obtain a silver-ammonia solution. Completely immerse the modified PET film in the silver-ammonia solution and activate it at 50°C for 10 minutes to obtain an Ag-activated PET film.
[0072] 3) Prepare an electroless copper plating solution based on the total volume of the electroless copper plating solution, with a concentration of 15 g / L copper sulfate, 45 g / L tetrasodium EDTA, 10 g / L formaldehyde, 15 g / L NaOH, 5 mg / L potassium ferrocyanide, 10 mg / L 2,2'-bipyridine, 30 mg / L polyethylene glycol 6000, and 5 mL / L tetrahydroxypropylethylenediamine. Completely immerse the Ag-activated PET film in the copper plating solution and plate the film at 50°C for 20 min to obtain a 6-μm composite copper foil with a thickness of 1 μm on both sides of the PET film.
[0073] The copper layer is dense, uniform and has no holes. The peel strength test shows that the copper layer bonding strength is 3.9N / cm. 2 , meeting the basic requirements of composite copper foil.
[0074] Comparative Example 1
[0075] Compared with Example 1, this comparative example differs in that: the step of “etching the surface of the PET film using O2 plasma with a power of 40 W, an oxygen flow rate of 30 sccm, and an etching time of 5 min” is not included.
[0076] Compared with Example 1, in this comparative example, the PET film was not subjected to plasma etching treatment, and the surface roughness of the PET film was low and lacked oxygen-containing groups, resulting in low wettability of the PET film to the NaOH solution and inability to undergo modification reaction with hydroxide ions. As a result, subsequent silver activation and copper chemical plating reactions could not proceed, and composite copper foil could not be prepared.
[0077] Comparative Example 2
[0078] Compared with Example 1, this comparative example differs in that: the step of "etching the surface of the PET film using O2 plasma with a power of 40 W, an oxygen flow rate of 30 sccm, and an etching time of 5 min" is not included; the modification time is changed from 60 min to 120 min, and the modification temperature is changed from 50°C to 70°C.
[0079] Compared with Example 1, although the temperature and time of NaOH modification, which also has a certain etching effect, are increased in this comparative example, due to the lack of plasma etching treatment, no oxygen-containing functional groups are generated on the surface of the PET film, and the surface is inert. As a result, subsequent silver activation and copper chemical plating reactions cannot proceed, and composite copper foil cannot be prepared.
[0080] Comparative Example 3
[0081] Compared with Example 2, this comparative example differs in that: the step of “preparing 100 g / L NaOH solution, completely immersing the functionalized PET film in the solution for 5 minutes after step 1), and modifying the film at 50°C for 60 minutes to obtain a modified PET film” is not included; and “completely immersing the modified PET film in the silver-ammonia solution” is replaced by “completely immersing the functionalized PET film in the silver-ammonia solution”.
[0082] Compared with Example 2, in this comparative example, the PET film was not modified with NaOH, and no active groups such as carboxyl / hydroxyl groups were produced on the surface of the PET film, which could not provide good binding sites for Ag+. As a result, there was a lack of catalytic sites during copper plating, and a copper layer with good bonding strength could not be deposited on the surface of the PET film.
[0083] Comparative Example 4
[0084] Compared with Example 2, this comparative example differs in that: "5 mg / L 2,2'-bipyridine concentration, 50 mg / L polyethylene glycol 6000 concentration, and 5 mL / L tetrahydroxypropylethylenediamine" in the chemical copper plating solution are omitted, and "2 mg / L potassium ferrocyanide concentration" is increased to "5 mg / L potassium ferrocyanide concentration".
[0085] Compared with Example 2, although the content of potassium ferrocyanide additive was increased in this comparative example, since only a single additive was used in the chemical copper plating solution, the stability of the copper plating solution decreased and self-decomposition occurred. The copper ion deposition was too fast, resulting in an increase in copper layer defects. The resulting copper layer was severely delaminated, and the interfacial bonding strength was significantly degraded. The peel strength test showed that the copper layer bonding strength was only 0.8 N / cm 2 .
[0086] Comparative Example 5
[0087] The difference between this comparative example and Example 5 is that the etching power is changed from 40 W to 10 W, and the etching time is changed from 5 min to 1 min.
[0088] Compared with Example 5, this comparative example cannot effectively functionalize the surface of the PET film due to the low power and short treatment time of the plasma etching treatment for the PET film. The surface roughness is low and there is a lack of oxygen-containing groups, resulting in low wettability of the PET film to the NaOH solution and inability to undergo modification reaction with hydroxide ions. As a result, subsequent silver activation and copper chemical plating reactions cannot proceed, and composite copper foil cannot be prepared by chemical plating.
[0089] Comparative Example 6
[0090] Compared with Example 2, this comparative example is different in that: the step of “preparing 1 g / L AgNO3 solution, slowly adding 1 wt% ammonia water until the precipitate completely disappears to obtain a silver ammonia solution, completely immersing the modified PET film in the silver ammonia solution, and activating at 50°C for 10 min to obtain an Ag-activated PET film” is omitted, and the step of “completely immersing the Ag-activated PET film in the copper plating solution” is replaced by “completely immersing the modified PET film in the copper plating solution”.
[0091] Compared with Example 2, this comparative example does not perform silver ammonia solution activation treatment on the PET film, resulting in a lack of metal active sites on the surface of the PET film that catalyze the deposition of copper ions, and cannot achieve the reduction and deposition of copper ions in the chemical copper plating solution on the surface of the PET film.
[0092] Comparative Example 7
[0093] This comparative example is different from Example 6 in that “modification at 50°C for 60 min” is replaced by “modification at 70°C for 70 min”.
[0094] Compared with Example 6, the NaOH modification treatment of the PET film in this comparative example used a treatment temperature that was too high and a time that was too long, resulting in severe etching of the PET film surface and wrinkling of the PET film, making it impossible to proceed to the next step of Ag activation and chemical copper plating, and thus unable to prepare a composite copper foil.
[0095] Comparative Example 8
[0096] Compared with Example 1, this comparative example differs in that: "preparing 1 g / L of AgNO3 solution, slowly adding 1 wt% ammonia water dropwise until the precipitate completely disappears to obtain a silver ammonia solution (at this time, the concentration of the silver ammonia solution is 0.6 g / L)" is replaced by "preparing 0.05 g / L of AgNO3 solution, slowly adding 1 wt% ammonia water dropwise until the precipitate completely disappears to obtain a silver ammonia solution (at this time, the concentration of the silver ammonia solution is 0.03 g / L)".
[0097] Compared with Example 1, in this comparative example, the silver ion concentration used for silver-ammonia activation of the PET film is too low, resulting in a low density of metal active sites on the surface of the PET film that catalyzes the deposition of copper ions. This cannot effectively catalyze the reduction and deposition of copper ions in the chemical copper plating solution on the surface of the PET film, and composite copper foil cannot be prepared by chemical plating.
[0098] Comparative Example 9
[0099] Compared with Example 1, this comparative example differs in that: "preparing a 1 g / L AgNO3 solution, slowly adding 1 wt% ammonia water dropwise until the precipitate completely disappears to obtain a silver ammonia solution (at this time, the concentration of the silver ammonia solution is 0.6 g / L)" is replaced by "a commercially available colloidal Pd activator, with a PdCl2 concentration of 0.1 g / L."
[0100] Compared with Example 1, this comparative example uses colloidal Pd activation solution instead of silver ammonia activation solution. However, since the active groups such as carboxylic acid generated on the surface of the PET film after plasma etching and NaOH modification cannot chemically coordinate with Pd ions, the colloidal Pd cannot activate the PET surface, so the next step of chemical copper plating cannot be carried out, and the composite copper foil cannot be prepared.
[0101] It should be noted that, according to the above-described embodiments of the present invention, those skilled in the art are fully capable of implementing the full scope of the independent claims and dependent claims of the present invention, using the same implementation processes and methods as the above-described embodiments; and that portions not described in detail herein are common knowledge in the art. However, the scope of protection of the present invention is not limited thereto; any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention are intended to be covered by the scope of protection of the present invention.
Claims
1. A method for preparing a PET-based composite copper foil, wherein the method adopts chemical plating to coat Cu on both sides of the PET, characterized in that: The specific steps include: 1) etching the PET film using O2 plasma, wherein the etching power is 20-100W, the oxygen flow rate is 5-40sccm, and the etching time is 1-10 minutes to obtain a functionalized PET film; 2) modifying the functionalized PET film, within 10 minutes of obtaining the functionalized PET film in step 1), placing the functionalized PET film in a NaOH solution having a concentration of 80 to 180 g / L for modification for 50 to 100 minutes to obtain a modified PET film; 3) activating the modified PET film, activating the modified PET film in a silver ammonia solution having a silver ion concentration of 0.1 to 5 g / L to obtain an activated PET film; 4) chemical copper plating, immersing the activated PET film obtained in step 3) in a chemical copper plating solution for chemical copper plating to obtain a PET-based composite copper foil, wherein the chemical copper plating solution comprises, based on the total volume of the chemical copper plating solution, two or more of 1-10 mg / L potassium ferrocyanide, 5-20 mg / L 2,2'-bipyridine, 20-50 mg / L polyethylene glycol 6000, 1-10 mL / L tetrahydroxypropyl ethylenediamine, 1-10 mg / L thiourea, 0.1-5 mg / L sodium lauryl sulfate, and 1 mg / L-10 mg / L 2,2-quinoline.
2. The method according to claim 1, wherein The method further includes a step of pre-treating the PET film before etching, wherein the pre-treatment comprises: immersing the PET film in anhydrous ethanol, degreasing the film under ultrasound with a power of 40 to 100 W for 1 to 10 minutes, taking the film out and rinsing it with deionized water, and then immersing the film in 1 to 10 wt% dilute sulfuric acid and ultrasound for 1 to 10 minutes.
3. The method according to claim 1 or 2, wherein: The thickness of the PET film is 4-20 μm.
4. The method according to claim 3, wherein: The temperature of the modification treatment is 25-70°C.
5. The method according to claim 4, wherein: The activation treatment is performed at a temperature of 26-60° C. and for a time of 1-10 minutes.
6. The method according to claim 5, wherein: The temperature of the chemical copper plating is 40-70° C., and the time is 10-30 minutes.
7. The method according to any one of claims 4 to 6, characterized in that The chemical copper plating solution also includes 2-15 g / L copper sulfate, 10-50 g / L tetrasodium ethylenediaminetetraacetic acid, 5-15 g / L formaldehyde, and 5-20 g / L NaOH.
8. A PET-based composite copper foil, characterized in that: The PET-based composite copper foil is prepared by the method according to any one of claims 1 to 7, the thickness of the copper foil on both sides of the PET is 0.6-1.5 μm, and the copper layer bonding strength of the PET-based composite copper foil is ≥3N / cm 2 .
9. Use of the PET-based composite copper foil as claimed in claim 8 in a negative electrode current collector.
10. Use of the PET-based composite copper foil according to claim 8 in a battery.
Citation Information
Patent Citations
Composite current collector and preparation method and application thereof
CN116207270A
Preparation method of composite copper foil
CN117702095A
PET copper foil, chemical plating preparation method and application thereof
CN119372733A
Current collector and energy storage device
CN119764455A